Coupling of a single tin-vacancy center to a photonic crystal cavity in diamond - Kuruma, Kazuhiro; Pingault, Benjamin; Chia, Cleaven; Renaud, Dylan; Hoffmann, Patrick; Iwamoto, Satoshi; Ronning, Carsten; Loncar, Marko (Applied Physics Letters, 2021)
We demonstrate optical coupling between a single tin-vacancy (SnV) center in diamond and a free-standing photonic crystal nanobeam cavity. The cavities are fabricated using quasi-isotropic etching and feature experimentally measured quality factors as high as ∼11 000. We investigate the dependence of a single SnV center's emission by controlling the cavity wavelength using a laser-induced gas desorption technique. Under resonance conditions, we observe an intensity enhancement of the SnV emission by a factor of 12 and a 16-fold reduction of the SnV lifetime. Based on the large enhancement of the SnV emission rate inside the cavity, we estimate the Purcell factor for the SnV zero-phonon line to be 37 and the coupling efficiency of the SnV center to the cavity, the β factor, to be 95%. Our work paves the way for the realization of quantum photonic devices and systems based on efficient photonic interfaces using the SnV color center in diamond.
CRIS-Team Scopus Importer:2023-04-20